Managing professional service delivery 9 rules for success - Mundt, Barry M.; Smith, Francis J.; Egan, Stephan D. Jr (Industrial and systems engineering series, 2014)
A stepbystep guide, this book describes in detail how to achieve the internal discipline and control necessary to manage professional service engagements and longterms success in the professional services industry. The authors draw on their many years of experience in the management field to layout procedures, tools, and techniques that address each step of the life cycle of an engagement from definition